Effectiveness of Government Business Incubators in Stimulating The Growth of UMKM in Makassar City - Zulkarnain, Muhammad Qadafi; Sahabuddin, Romansyah; Amin, Andi Nurzakiah; Sulolipu, Andi Annisa (Economics and Business Journal (ECBIS), 2025)
This study aims to analyze the effectiveness of the Government Business Incubators in encouraging the growth of MSMEs in Makassar City. Using a qualitative approach and case study research design, this study explores the experiences and perceptions of MSME actors and incubator managers regarding the impact of incubation on their business development. Data were collected through in-depth interviews, participant observation, and documentation related to the incubation program run by Makassar Technopark and Makassar City Business Incubator. The results of the study indicate that business incubators have a positive impact on improving managerial skills, wider market access, and strong business networks for MSMEs. However, there are challenges related to the suitability of training materials to the needs of specific sectors, difficulties in accessing capital, and limited time that MSME actors can invest in participating in the incubation program. Lack of ongoing mentoring after the incubation is complete is also one of the obstacles faced by business actors. Therefore, this study recommends adjusting the incubation program to be more relevant to the needs of each MSME sector, as well as increasing post-incubation support to ensure business sustainability.